Zinc-ion-mediated self-assembly of forky peptides for prostate cancer-specific drug delivery. Issue 37 (20th April 2018) - Tao, Mingtao; Xu, Keming; He, Suyun; Li, Hongmei; Zhang, Li; Luo, Xuefang; Zhong, Wenying
Abstract : A hexapeptide with a unique forky structure can form hydrogels triggered by zinc ions for prostate cancer therapy. Abstract : A novel forky peptide was designed and synthesized. The peptide self-assembled into supramolecular hydrogels triggered by zinc ions (ZIs). The hydrogels were designed for a drug delivery system (DDS), loaded with docetaxel and applied for the therapy of prostate cancer. In this research, we have discussed the response mechanism and evaluated the anticancer effect of the DDS.